ISLAMIC SOCIAL REPORTING AND FIRM VALUE ISLAMIC BANKING COMPANY WITH RGEC METHOD - Puji Nurhayati; Erisa Putri Wardani; Desy Nur Pratiwi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The company's value is significant for investors because it can reflect its condition. Maximizing company value can be done by maintaining the level of bank health. The study aimed to determine the determinants of Risk Profile, Good Corporate Governance, Earnings, and Capital (RGEC) on company value. As well as the influence of moderation between RGEC variables on company value through Islamic Social Reporting. This research was conducted on 13 Islamic general banks in Indonesia. The study sample was 91 data. The data used is secondary data. This type of research is descriptive quantitative with multiple regression analysis techniques of panel data. The sampling technique is carried out by purposive sampling method. The result of this study is that the risk profile has a positive and significant effect on the company's value. GCG does not influence company value. Earnings have a negative and powerful influence. Capital does not affect the value of the company. Meanwhile, ISR can moderate the risk profile and gain company value. However, ISR is unable to negotiate GCG and capital toward company value. Keywords: Risk Profile, Good Corporate Governance, Earning, Capital, Financial Distress